ADP-induced platelet reactivity and bleeding events in patients with acute myocardial infarction complicated by cardiogenic shock. (3rd April 2022) - Scherer, Clemens; Lüsebrink, Enzo; Kupka, Danny; Stocker, Thomas J.; Stark, Konstantin; Kleeberger, Jan; Orban, Mathias; Kellnar, Antonia; Petzold, Tobias; Deseive, Simon; Krieg, Kathrin; Würbel, Sara; et al.
Abstract: While previous reports showed ADP-induced platelet reactivity to be an independent predictor of bleeding after PCI in stable patients, this has never been investigated in patients with cardiogenic shock. The association of bleeding events with respect to ADP-induced platelet aggregation was investigated in patients undergoing primary PCI for acute myocardial infarction complicated by cardiogenic shock and with available on-treatment ADP-induced platelet aggregation measurements. Out of 233 patients, 74 suffered from a severe BARC3 or higher bleed. ADP-induced platelet aggregation was significantly lower in patients with BARC≥3 bleedings ( p < .001). Multivariate analysis identified on-treatment ADP-induced platelet aggregation as an independent risk factor for bleeding (HR = 0.968 per AU). An optimal cutoff value of <12 AU for ADP-induced platelet aggregation to predict BARC≥3 bleedings was identified via ROC analysis. Moreover, the use of VA-ECMO (HR 1.972) or coaxial left ventricular pump (HR 2.593), first lactate (HR 1.093 per mmol/l) and thrombocyte count (HR 0.994 per G/l) were independent predictors of BARC≥3 bleedings. In conclusion, lower on-treatment ADP-induced platelet aggregation was independently associated with severe bleeding events in patients with AMI-CS. The value of platelet function testing for bleeding risk prediction and guidance of anti-thrombotic treatment in cardiogenic shock warrants further investigation.